A survey of the dialect geography of four towns and two cities in Negros Occidental Escalante, Hinigaran, Ilog, Sipalay, Bacolod City and Cadiz City - Jaena, Angelina Juaneza 1928- ([Quezon City s.n.], 1970)
The aim of the study is to make a survey of the dialect geography organized in terms of the variables of lexical and phonological features of the six communities of Negros Occidental, namely: Escalante, Cadiz City, Bacolod City, Hinigaran, Ilog, and Sipalay. The study is primarily concerned with finding the degree of social and locational distribution of dialectal variations among specific age levels of speakers- middle-aged and adolescents, each including informants who are highly educated, better educated, and poorly educated or uneducated. Findings of the study reveal that mutual intelligibility and correspondence range from high to very high in five communities except Escalante which differed markedly because of the mixed character of its dialect due to the influence of Cebuano. Nevertheless, the probability in misunderstanding or misinterpretation is considered low.
Thesis (M.A.T.English)--University of the Philippines
Typescript
Keywords: Bisaya language -- Dialects -- Bisaya language -- Maps; Negros Occidental -- Languages -- Maps